2018
DOI: 10.1051/matecconf/201815002008
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals (Fe, Cu, and Cr) Removal from Wastewater by Moringa Oleifera Press Cake

Abstract: Abstract. The consumption of water nowadays is increasing and the wastewater from variety of industry and domestic are increasing as well. If this wastewater is being untreated, it will be wasted and the chemicals inside the water especially heavy metal are harmful to the living organism. There are few conventional method used to treat the wastewater but most of them are costly, hence, natural coagulant is introduced in this study. One of the multipurpose tree Moringa oleifera, (MO) which is environmental frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The results pointed that the removal efficiency of Cr, Pb, and Cd was higher than 98% in the pH range of 2 to 8, indicating that the natural coagulant could work in a wide pH range. In a study, (Ali and Seng (2018) investigated the removal of heavy metals from river water samples using Moringa oleifeara press cake. The results indicated that the removal efficiency of Cr, Cu and Fe was 93.73, 88.86 and 66.99%, respectively.…”
Section: Abiyu Et Al (mentioning
confidence: 99%
“…The results pointed that the removal efficiency of Cr, Pb, and Cd was higher than 98% in the pH range of 2 to 8, indicating that the natural coagulant could work in a wide pH range. In a study, (Ali and Seng (2018) investigated the removal of heavy metals from river water samples using Moringa oleifeara press cake. The results indicated that the removal efficiency of Cr, Cu and Fe was 93.73, 88.86 and 66.99%, respectively.…”
Section: Abiyu Et Al (mentioning
confidence: 99%
“…One study of Ali and Tien Seng, (2018) used Moringa Oleifera to remove heavy metals from wastewater. The study investigated Fe, Cu, and Cr at concentrations of 10000 ppm, 5000 ppm, and 15000 ppm, respectively, and found that the plant-based coagulant showed a removal efficiency of 69.99% Fe, 88.86% Cu, and 93.73% Cr.…”
Section: Application Of Plant-based Natural Coagulants In Water Treat...mentioning
confidence: 99%
“…Without water, there would be no life (Abujazar et al, 2018;Asrafuzzaman et al, 2011;Desta and Bote, 2021;Nath et al, 2019). In recent times, water consumption has increased due to industrialization and urbanization, as well as population growth (M. Y. D. Alazaiza et al, 2022;Ali and Tien Seng, 2018;Tang et al, 2016;Wang et al, 2021), and accordingly, wastewater from the various industrialization and urbanization activities is also increasing, making access to clean and safe water a critical issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A part remains after oil seed extraction (with minimal production costs), moringa seed residue (MOSr), also known as press cake, seed cake or cake residue, which retains mainly the positively charged protein [19]. MOSr serves as a scavenger for heavy metal removal, as a natural coagulant for wastewater treatment and has also been found to possess antibacterial properties [20,21].…”
Section: Introductionmentioning
confidence: 99%